Effect of 28-Day Repeated Oral Administration of Flavonoid-Rich Fraction of Detarium microcarpum (Fabaceae) Stem Bark on Liver and Kidney Parameters and Other Biomarkers in Wistar Rats - M. M, Ahmad; M. I., Maje; .J, Ya’u; A. K, Umar; M. U., Abba (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
Although plants are the major sources of drug, many plants were found to be very toxic when administered systemically. Ethnobotanical surveys reported how reputable Detarium microcarpum is in treating many diseases African countries. To evaluate the effect of 28-day repeated oral administration of flavonoid-rich fraction of Detarium microcarpum stem bark extract on biochemical parameters in Wistar rats. Wistar rats were divided into four groups of five animals each and administered different doses (250, 500 and 1000 mg/kg) of flavonoid-rich fraction via oral route to group II, III and IV respectively while group I received normal saline Body and relative organ weight, liver biomarkers, biochemical (liver and kidney function) parameters, , electrolytes (K, Na, HCO, Cl), and oxidative stress (SOD, MDA, GSH etc.)markers were measured. No significant (P>0.05) increase in body and relative organ weight, liver and kidney function biomarkers (except in BUN at the dose of 1000 mg/kg), oxidative stress markers, electrolytes level and hematological (WBC, RBC, Platelets etc.) parameters in the alkaloid-rich fraction treated rats compared to the normal saline treated group. The flavonoid-rich fraction of Detarium microcarpum stem bark produces no alteration on biochemical and hematological parameters except on oxidative stress markers at higher doses in Wistar rats which, indicated its relative safety.